Jawabanmu

2014-04-29T15:19:34+07:00
1.
f(-1) = -1p + q = -5
f(4)  = 4p + q = 5
------------------------------------  -
-5p = -10
p = 2

4.2 + q = 5
q = 5 - 8 = -3

f(-6) = 2.-6 + -3 = 12 + (-3) = Jawab sendiri :v

2.
f(-4) = -2.4 + 5 
       = -8 + 5
       = -3
2014-04-29T15:23:37+07:00
1.    -1      -5
        4       5  -
     - 5y = -10x + ( -1 x 5) - ( -5 x 4)
     - 5y = -10x + 15              (:  -5)
        y  =  2x - 3
Jadi Nilai f(6) = 2 x 6 - 3 = 9

2. f(-4) = -2 x 4 + 5 = -3
ini cara cepat saya
Komentar sudah dihapus